A study of eating habits among students at the Faculty of Education, Universiti Teknologi MARA / Mohd Rizuan Ibrahim - Ibrahim, Mohd Rizuan (2014)
This study was carried out to assess the eating habits among university students. There were 100 respondents involved in this study; the people who were involved are students of Faculty of Education in UiTM Shah Alam, Selangor. The researcher prepared a set of questionnaire which consisted of seventy four items. Questionnaires were distributed randomly in order to obtain information and responses regarding their eating habits and eating pattern . The survey is based on the source of "Eating Behaviour Pattern Questionnaire (EBPQ)", which was subsequently adapted to meet the needs of the study. The data collected via the questionnaire was calculated manually and the findings were tabulated, and then presented in an orderly and easyto- read manner in SPSS system. The findings of the study observed that healthy eating habits and patterns are practiced among students in their daily live . This is showed through their Body Mass Index (BMI) range which averagely stated on Normal (18.5-24.9) range. The results also showed that the relationship between the frequency of meal intake by the students and their Body Mass Index (BMI) is not significant. This study suggested that healthy eating habits should continue praticed by universities students. Through caimpaign and seminar to universities students, it could be increase their awareness on healthy eating habits.